Exilic Returns: The Ten Tribes in Early Modern Reflections on Jewish History - Schatz, Andrea (Political theology, 2025)
This article investigates how narratives about the Ten Tribes in sixteenth-century Italy supported Jewish reflections on exile that were firmly oriented towards the diasporic present and rather ambivalent regarding a return to the ancestral land. The article outlines medieval traditions about the “shadow exile” of the Ten Tribes that were relevant, when narratives about them were re-written in the early modern world. It then analyses visions of an only partial return to the Holy Land and the intriguing transformation of the Tribes from warriors into merchants trading in the early colonial world in Abraham Farissol’s Iggeret orḥot ‘olam. Finally, it discusses the ambivalent legitimization of exilic continuity without return in Azariah de’ Rossi’s Me’or ‘enayim. The article shows how the Ten Tribes could serve to encourage a hopeful (re-)turn to the present moment, while keeping critical perspectives on exile inscribed in early modern ways of creating a diasporic home.